Strategi Komunikasi Politik Perempuan di Maluku : Pela dan Gandong sebagai Modal Sosial - Kimono, Hendri (Jurnal Inovasi Komunikasi, 2025)
This study is motivated by the strong patriarchal culture in Maluku, which limits women's roles in politics. Despite efforts to increase female political participation, women still face social and structural barriers. Politics is often perceived as a masculine domain, making it even more challenging for women to gain legitimacy and support. In this context, female politicians in Maluku must develop effective communication strategies to navigate these challenges. This research aims to explore the political communication strategies of female politicians in Maluku and identify the factors influencing their success or failure. A qualitative case study approach was used, with data collected through in-depth interviews with female politicians, activists, and political observers, as well as document analysis and field observations. The findings reveal that, despite significant challenges, female politicians in Maluku adapt by leveraging local values such as pela and gandong. Community solidarity and social networks based on traditional customs play crucial roles in strengthening their political positions. Additionally, support from women's groups and political organizations helps them overcome structural barriers. This study concludes that women's political communication in Maluku is a complex adaptation to the local socio-cultural context. By utilizing local social capital, they strengthen their political standing in a male-dominated environment.